Urbanonymic Terminology: Systems and Problems - R. V. Razumov; S. O. Goryaev (Научный диалог)
The article is focused on the problem of ordering and adaptation of modern Russian onomastic terminology to its foreign, especially Western European versions. The material for the analysis was the terms and their definitions from the Dictionary of Russian Onomastic Terminology by N. V. Podolskaya, the list of basic terms of ICOS (International Council of Onomastic Sciences) and lists of basic terms and their definitions in English, French and German. The article shows the history of the Russian urbanonymic terminology, noting its systematic nature. At the same time, its shortcomings are pointed out: emergence of new meanings of the term urbanonym that are contrary to the recommendations of the dictionaries and are not included in the conceptual field of the toponym, which is a hypernym for it. The authors note the difficulties in adapting the Russian terminology under Western European, its inconsistency: the term odonym actually acts as a synonym of the Russian term urbanonym . At the same time, it can be argued that in the Western European tradition, in contrast to the Russian one, the complete concept of urbanonym and its hypero-hyponymic relations is missing. The revision of the list of basic ICOS onomastic terms is needed, introduction of a term similar to the Russian urbanonym , its precise definition, definition of the scope of the specific terms and its components.